PERAN GURU DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS - Buulolo, Delisokhi (Universitas Nias Raya, 2024)
The problem of this research is that student learning outcomes in social studies subjects tend to be low. The research objectives are 1) Describe the factors that cause low student learning outcomes. 2) Describe the role of teachers in improving student learning outcomes in social studies subjects. Type of qualitative research. The data sources used are primary and secondary data. Data collection techniques through interviews, observation, documentation. Research results: 1) There are two factors causing low student learning outcomes, namely internal factors including students' lack of interest in lessons, students' lack of concentration during the learning process, students' low understanding of concepts, students' lack of discipline in learning. External factors include a lack of infrastructure and learning facilities, as well as a lack of attention from parents. 2) The role of the teacher in improving student learning outcomes is as a corrector, as an inspirer, as an informator, as an organizer, as a motivator, as an initiator, as a facilitator, as a guide, as a demonstrator, as a class manager, as a mediator, as a supervisor, and as an evaluator. Conclusion: The role of teachers as educators and instructors includes all efforts that encourage, guide, awaken, direct, understand the potential of students, vary learning methods, and use learning media as support in the learning process, providing optimal service to students in the learning process. carry out a more effective learning process and create a more enjoyable learning atmosphere so that student learning outcomes increase. Suggestions 1) For teachers, they should further develop learning methods or strategies that can help students develop their competencies and abilities and build knowledge actively. 2) Students should focus more on learning, reduce playing hours and increase study hours at home.